Analisis Pengaruh Nilai Pelanggan, Kualitas Pelayanan Dan Kedakatan Emosional Terhadap Loyalitas Nasabah ( Studi Kasus Pada Bank Bri Kantor Cabang Unisma ) - Nuryati Nuryati; Rois Arifin; Kartika Rose Rachmadi (UNIVERSITAS ISLAM MALANG, 2023)
Abstract The population in this study is the customers of Bank BRI UNISMA Malang Branch Office savings. The samples taken were 98 respondents using the Non-Probability Sampling technique with the Purposive Sampling approach, namely sampling using the Slovin formula, while the sampling criteria were respondents to BRI bank savings customers, UNISMA Malang Branch Office, domiciled in Malang / Malang resident and 17 years old . Based on the research results, the regression equation is obtained as follows: Y = 5,832 X₁ 0.661 + 0.712 X₂ +0.502 X₃. Based on statistical data analysis, the indicators in this study are valid and the variables are reliable. In testing the classical assumptions, the multicollinearity independent regression model, there is no heteroscedasticity and normal distribution. The individual order of each of the most influential variables is the Service Quality variable with a regression coefficient of 0.712, then the Customer Value variable with a regression coefficient of 0.661, then followed by the Emotional Closeness variable with a regression coefficient of 0.502. BRI Bank UNISMA Malang Branch Office needs to maintain elements that have been considered good by customers and improve things that are still lacking Keywords: Customer Value, Service Quality, Emotional Closeness, Loyalty